2019
DOI: 10.1021/acs.jpcc.9b03335
|View full text |Cite
|
Sign up to set email alerts
|

Well-Ordered Monolayer Growth of Crown-Ether Ring Molecules on Cu(111) in Ultra-High Vacuum: An STM, UPS, and DFT Study

Abstract: Crown-ether (CR) ring molecules are known as host molecules for capturing guest species inside the ring. So far CR molecular films have only been grown by drop-casting a CR solution on an inert substrate in air which offers little control over the molecular structure. Here we report the successful growth of a well-ordered CR molecular array on an atomically flat and clean noble metal Cu(111) substrate at 300 K in ultra-high vacuum (UHV), using 4,4′,5,5′-tetrabromodibenzo[18] crown-6 ether (Br-CR). The adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The experiment was performed with a home-built low-temperature STM instrument at 4.6 K under UHV. The setup consists of introduction, preparation, and analytical chambers with a base pressure of <10 –8 Pa (see details in refs ). A UHV cryostat (CryoVac), including an outer liquid nitrogen tank (8 L) and an inner helium tank (4 L), is docked on the analytical chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was performed with a home-built low-temperature STM instrument at 4.6 K under UHV. The setup consists of introduction, preparation, and analytical chambers with a base pressure of <10 –8 Pa (see details in refs ). A UHV cryostat (CryoVac), including an outer liquid nitrogen tank (8 L) and an inner helium tank (4 L), is docked on the analytical chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Cu­(111) Preparation . The Cu(111) single crystal was cleaned by repeated cycles of Ar + sputtering (1.0 kV, 0.80 μA) for 15–30 min with subsequent annealing (820 K) (see details in refs and ). The cleanliness of the substrate was checked using LEED.…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical framework built from the first-principles simulations is used to understand the significance of chemical bonds in generating rich and unique geometrical structures as well as custom-tailored electronic and magnetic properties. The theoretical predictions about the geometrical structures, band structures, van Hove singularities, and charge/spin-density distributions can be verified through high-resolution scanning tunneling microscopy/transmission electron microscopy (HRSTM/TEM) [28,29], angle-resolved photoemission spectroscopy (ARPES) [30], scanning tunneling spectroscopy (STS) [31], and STM spin excitation spectroscopy [32], respectively.…”
Section: Introductionmentioning
confidence: 93%
“…38,39 The numerical settings were the same as in our previous study on BrCR/Cu(111). 24 We used the PBE exchange-correlation potential and Grimme's DFT-D2 van der This journal is © The Royal Society of Chemistry 2024…”
Section: Dft Calculationmentioning
confidence: 99%
“…However, it was recently shown that the crown ring can be unfolded when BrCR forms a self-assembled monolayer (SAM) ring array on a metal Cu(111) surface. 24 Herein, Co was selected as the ''guest'' since the growth, electronic, and magnetic structures of bilayer triangularshape Co nanoislands on Cu(111) substrate are well known. [25][26][27][28] Although there are reports on the adsorption of Co ions on crown ether molecules in bulk, 29 no studies have been conducted on crown ether and metal clathrate compounds on solid surfaces in a vacuum.…”
Section: Introductionmentioning
confidence: 99%